PERAN MEDIASI KNOWLEDGE SHARING DAN INOVASI PADA PENGARUH BUDAYA PERUSAHAAN DAN KEPEMIMPINAN TRANSFORMATIONAL PADA KINERJA PEGAWAI - Padmo wiyono, Setiyawan; Suhana (Universitas Bina Taruna Gorontalo, 2025)
This research aims to examine the influence of organizational culture and transformational leadership on employee performance mediated by knowledge sharing and innovation at PT PLN (Persero) UID Suluttenggo. This quantitative research uses a questionnaire with simple random sampling techniques to collect data. The questionnaire was measured using a Likert scale of 1 – 5 which was distributed with the help of Google Form as a survey medium. The respondents in this research were PLN UID Suluttenggo employees in all their work units, totaling 306 respondents. Data were analyzed and processed using the SPSS – 24 method to test hypotheses. The research results show that organizational culture and transformational leadership have a positive and significant influence on knowledge sharing, innovation and employee performance. Apart from that, this research also shows that knowledge sharing and innovation can mediate the influence of corporate culture and transformational leadership on employee performance. The research results show that the role of corporate culture, transformational leadership, knowledge sharing and innovation is very important in the performance of PLN UID Suluttenggo employees.